The third Psyche of Polish literature. Anna Olimpia Mostowska’s “Miłość i Psyche” in comparison with seventeenth-century Polish translations of Apuleius’ tale (a preliminary study) - Pasikowska, Zuzanna (Melusine. Old Literature and Culture, 2025)
The main subject of the article is a short story written by Anna Olimpia Mostowska titled “Miłość i Psyche”, which is a forgotten translation of an ancient tale from Apuleius’ “Metamorphoses”. The analysis compares this text with two seventeenth-century Polish versions of Cupid and Psyche’s story – the fourth canto of Giambattista Marino’s “L’Adone” in anonymous translation and Jan Andrzej Morsztyn’s poem “Psyche”. The author of the article points out that even though the analyzed texts retell the same story, they differ significantly in terms of their origin, literary genres, poetics, and plot. The study suggests that some differences may arise from the fact that “Miłość i Psyche” is the first Polish adaptation of Apuleius’ story written by a woman. The article aims to bring Mostowska’s work to light and integrate it into future studies related to the Polish reception of the ancient tale.